The lady and the highwayman - Eden, Sarah M (Proper romance., 2019)
"Authors Elizabeth Black and Fletcher Walker go head-to-head as rival writers of Victorian Penny Dreadfuls. As an upper class schoolteacher, Elizabeth must write under the pseudonym "Mr. King" in order to keep her identity a secret, while former street urchin Fletcher is determined to uncover the truth behind this up-and-coming new talent. But the more time they spend together, the more she loses her heart to him. It's author against author where readers, reputations, and romance are all on the line."--Provided by the publisher.